Constitutional Constraints on Regulatory Asymmetries in Telecommunications Regulation in Brazil - Iorio Aranha, Marcio; Schertel Mendes, Laura; Campos Soares da Fonseca, Gabriel (Law, State and Telecommunications Review, 2024)
[Purpose] This article aims to analyze the legal-constitutional validity of the new wording of the General Regulation of Consumer Rights for Telecommunication Services (RGC) as a measure of regulatory asymmetry promoted by the National Telecommunications Agency (Anatel). [Methodology/approach/design] To this end, we examine the role of the Agency as a normative agent empowered to establish asymmetries in the regulation of the sector, which, however, must respect the principles of equality, free competition, consumer rights, and the core essence of weighted rights. [Results] The analysis of the existing asymmetries shows that the majority of telecommunications services users in Brazil are not protected by the RGC. As a consequence, the RGC either does not recognize rights considered essential to them, or creates rights of enjoyment considered superfluous, burdening only the major operators. Consequently, the measure is not in line with the responsive regulation model adopted by Anatel. [Practical implications] The article points to the need to review either the regulatory asymmetries granted to Public-Private Partnerships (PPPs), as they are, in fact, institutional guarantees for consumer protection and therefore non-negotiable, or the regime of rights and obligations imposed by the RGC on providers as a whole, which requires compliance with measures that, not being essential to consumers, could not be demanded from operators in general.